Optimization of coil spring by finite element analysis method of automobile suspension system using different materials. (2021) - Kushwah, Sagarsingh; Parekh, Shreyashkumar; Mangrola, Mehul
Abstract: In vehicles, problems happen while driving on bumps on road & improper road conditions. The objective of this research is to optimize the performance of the helical coil spring used in the suspension of cars of hatchback segment by varying different parameters of the spring to make it more efficient than the existing coil springs used in current hatchbacks. The helical compression spring utilized in mechanical system or shock may be a machine designed to free or damp shock impulse and dissipate mechanical energy. A helical compression coil spring which is used in four-wheel cars which are belonging in the hatchback category of the Indian automotive market. It is observed that the vehicle drifts towards one side due to the high weight of the suspension system and loads. This problem can be solved by redesigning and optimizing the suspension spring. This project consists of analytical methods and Finite Element Analysis completed from modeling, meshing, and post-processing of front suspension springs to validate calculations. By using Finite Element Analysis (FEA), the structural strength of the coil spring is also evaluated in present work. Based on theoretical and software result comparison is made for the optimum result which meets all requirements which were suggested.